? - Mantel-Teeuwisse, Aukje (Arhiv za farmaciju, 2022)
Digital health technologies such as health apps, wearables, e-prescribing and digital therapeutics are rapidly emerging. These technologies may aid pharmacists in their evolving role as health care professionals with a focus on pharmaceutical care, but digital literacy skills are needed for full benefits. The aim is to provide insight into educational needs by the current and future workforce and provide examples of applications of digital health technologies in pharmaceutical care. Needs were assessed by an online global survey (2020) among faculty of pharmacy schools, pharmacy students and practitioners, led by the International Pharmaceutical Federation (FIP). The full methods have been described elsewhere. Examples of applications are taken from the Dutch setting. Over 1000 respondents from 91 countries completed the survey, including 260 faculty representatives, 274 students and 526 practitioners. Needs were similar among students and practitioners and included both knowledge about specific technologies (especially apps, electronic health records and telemedicine/remote patient monitoring) as well as concepts such as ethics, compliance, data privacy and security. Many opportunities for integrating digital health technologies in pharmaceutical care exist, but education of current and future pharmacists is needed to create a digitally enabled workforce that can capitalize on the benefits of digital technologies.